A pH-switched Pickering emulsion catalytic system: high reaction efficiency and facile catalyst recycling. Issue 34 (30th March 2015) - Huang, Jianping; Yang, Hengquan
Abstract : A smart Pickering emulsion catalytic system is first constructed, which not only exhibits fivefold reaction rate enhancement effects in comparison to the conventional biphasic reactions but also can be demulsified by tuning pH at the end of reaction, allowing for in situ recycling nanoparticle catalysts. Abstract : A smart Pickering emulsion catalytic system is constructed, which not only exhibits fivefold reaction rate enhancement effects in comparison to the conventional biphasic system but also can be facilely demulsified by tuning pH, allowing for in situ recycling nanocatalysts.